Foliar nutrient concentrations and stoichiometry should not be assumed to diagnose nutrient limitation - Dan Binkley; José Luiz Stape; Timothy J. Albaugh (Ecological Processes)
Abstract Nutrient concentrations in foliage are often used to infer whether growth of a species at a particular site is likely limited by low supply of soil nutrients. Sometimes ratios of nutrient elements (stoichiometry) are thought to be useful, as if a higher supply of one element might somehow physiologically alleviate, or interfere with, a low supply of another. The growth of most forests is indeed commonly limited by low supplies of nutrients in soils, but foliar chemistry has proven unable to discern nutrient limitations. We illustrate this conclusion using two large, regional experiments with Eucalyptus in Brazil and loblolly pine (Pinus taeda L.) in the southeastern USA. In both cases, most sites showed profitable increases in growth after fertilization, and nutrient concentrations in foliage differed substantially across sites. However, foliar nutrient concentrations (and stoichiometric ratios) did not provide useful information about forest growth responses. We urge authors, reviewers, and editors not to expect foliar chemistry to be a useful tool for diagnosing nutrient limitations in forests, unless strong, local evidence demonstrates a reliable association.